111k views
3 votes
4x + 4(3 - 2×) = 2(4x + 2)/4 + 5
Solve this equation

User Kickaha
by
5.4k points

1 Answer

6 votes

Answer:

x=1

Explanation:

Factor out the common term 22.

4x+4(3-2x)=2\times \frac{2(2x+1)}{4}+5

4x+4(3−2x)=2×

4

2(2x+1)

​ +5

2 Simplify 2\times \frac{2(2x+1)}{4}2×

4

2(2x+1)

​ to 2x+12x+1.

4x+4(3-2x)=2x+1+5

Simplify 2x+1+5 to 2x+6.

4x+4(3-2x)=2x+6

Expand.

4x+12-8x=2x+6

Simplify 4x+12-8x to -4x+12.

-4x+12=2x+6

Add 4x to both sides.

12=2x+6+4x

Simplify 2x+6+4x to 6x+6.

12=6x+6

Subtract 6 from both sides.

12-6=6x

Simplify 12−6 to 6.

6=6x

Divide both sides by 6

1=x

Switch sides.

x=1

User Innova
by
4.5k points